DIGITAL DENTISTRY AND 3D PRINTING TECHNOLOGIES: REVOLUTIONIZING DENTAL PROSTHETICS AND ORTHODONTICS - Fazliddin Arzikulov; Samandar Abduvohidov (Web of Journals Publishing, 2025)
The field of dentistry has undergone a major transformation with the integration of digital technologies and 3D printing. Traditional methods for creating dental prosthetics and orthodontic appliances are being increasingly replaced by computer-aided design (CAD), computer-aided manufacturing (CAM), intraoral scanning, and additive manufacturing techniques. These technologies enable highly accurate, customized, and efficient treatment planning, improving patient outcomes while reducing production time and material waste. 3D printing, in particular, allows rapid fabrication of crowns, bridges, dentures, surgical guides, and clear aligners with exceptional anatomical precision. It also supports minimally invasive procedures, enhances esthetic results, and improves overall patient satisfaction. Beyond conventional applications, the future of digital dentistry includes bioprinting of tissues, integration with artificial intelligence (AI) for predictive treatment planning, and automation of workflow processes, which may revolutionize personalized dental care. Despite the benefits, challenges remain, such as high initial investment costs, the need for specialized training, and standardization of digital protocols across clinics. This article reviews the current advancements in digital dentistry and 3D printing, evaluates their clinical applications, and discusses future trends for optimizing dental prosthetics and orthodontic treatment.
Keywords: Digital Dentistry, 3D Printing, CAD/CAM Technology, Dental Prosthetics, Orthodontics, Bioprinting, Intraoral Scanning, Patient-Centered Care, Workflow Automation, Personalized Dentistry.